2016
DOI: 10.1007/s00343-017-5352-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, salinity, and irradiance on the growth of harmful algal bloom species Phaeocystis globosa Scherffel (Prymnesiophyceae) isolated from the South China Sea

Abstract: Blooms of Phaeocystis globosa have been frequently reported in Chinese coastal waters, causing serious damage to marine ecosystems. To better understand the ecological characteristics of P . globosa in Chinese coastal waters that facilitate its rapid expansion, the eff ects of temperature, salinity and irradiance on the growth of P . globosa from the South China Sea were examined in the laboratory. The saturating irradiance for the growth of P . globosa ( I s ) was 60 μmol/(m 2 •s), which was lower than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The field investigation was conducted in the north Beibu Gulf, where blooms of P. globosa have occurred frequently during both winter and summer in the last decades (Wang et al ., 2010; Xu et al ., 2017). Samples were collected from four sites, ZN1‐2 (N 20.1692, E 108.6187), ZN2‐2 (N 20.5006, E 108.6244), ZN3‐4 (N 20.8183, E 109.3290) and ZN4‐5 (N 21.1744, E 109.6005) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The field investigation was conducted in the north Beibu Gulf, where blooms of P. globosa have occurred frequently during both winter and summer in the last decades (Wang et al ., 2010; Xu et al ., 2017). Samples were collected from four sites, ZN1‐2 (N 20.1692, E 108.6187), ZN2‐2 (N 20.5006, E 108.6244), ZN3‐4 (N 20.8183, E 109.3290) and ZN4‐5 (N 21.1744, E 109.6005) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Cao et al found that MC could effectively flocculate and settle P. globosa solitary cells and colonies [ 20 ], but the effects of MC on P. globosa cell growth and colony formation remained unclear. As previously mentioned, P. globosa tends to form colonies in resistance to environmental stresses [ 34 , 35 ], and MC presented indirect effects in controlling the growth of HABs [ 29 , 30 , 31 ]. Therefore, we assumed that the growth and colony formation of the remaining cells might be inhibited after MC treatment, which could potentially prevent the P. globosa blooms.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, blooms of P. globosa have occurred frequently in coastal regions of southern China during both winter and summer, greatly impacting local fishing, farming, and environmental health ( Wang et al, 2006 , 2010 ). Recently, P. globosa blooms have occurred frequently along the Beibu Gulf coast ( Liu et al, 2015 ; Qin et al, 2016 ; Xu et al, 2017 ), a historically important region for the economies of China and Vietnam because of the abundant and diverse marine resources ( Zheng et al, 2012 ). As such, there is a need to understand the impact of algal blooms and the mechanisms of their impact on ecosystem health.…”
Section: Introductionmentioning
confidence: 99%